Standarisasi Ekstrak Etanol Daun Saga (Abrus precatorius L.) Sebagai Minuman Tradisional - Bheta Sari Dewi; Beny Maulana Satria; Ayu Werawati; Sayyidah (Jurnal Sains Farmasi Dan Kesehatan, 2024)
Saga has the species name Abrus precatorius L, which belongs to the Fabaceae family. The leaves of this plant are widely used by people as traditional medicine to reduce fever and cough. The aim of this research is to examine the use of saga leaf extract as a traditional drink that meets quality standards, so that the standardization process for this extract is carried out by determining specific parameters and non-specific parameters. The method used is maceration extraction using 70% ethanol. Specific parameters carried out include extract identity, organoleptic and phytochemical tests. Non-specific parameters used include ash content, acid soluble ash content, acid insoluble ash content, water content and drying shrinkage. The results obtained were a yield of 16.15% thick saga leaf extract, thick texture, greenish black in color, with a distinctive aroma. The extract contains saponin, alkaloid, tannin and flavonoid compounds. The results of non-specific parameter tests showed that the ash content was 2.17%, the acid soluble ash content was 2.17%, the acid insoluble ash content was <0.02%, the water content was 12.30% and the drying loss was 12.30%. The conclusion is that the research results meet extract quality standards. The data is expected to provide additional information regarding ethanol extract of saga leaves as a traditional medicine.